Algorithmic management on digital labour platforms: A systematic literature review - Azevedo, Érika Sabrina Felix; Souza, Diego Fillipe de; Mendonça, José Ricardo Costa de (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This study aims to understand algorithmic management in digital work platforms. To this end, a systematic literature review was conducted in the main databases of the Administration field. Initially, 912 studies were surveyed that went through inclusion and exclusion criteria, resulting in a corpus of 39 articles. The results produced demonstrated the existing research perspectives, definitions and conceptualizations, their similarities and discrepancies, assisting the development of future research and leading researchers in the area. The contribution of this study consists in making the conceptualization process of algorithmic management more understandable and systematic, guiding towards a uniform direction instead of scattered perspectives.